Monitoring and control of forest seedling quality in Europe - Mataruga, Milan; Cvjetković, Branislav; De Cuyper, Bart; Aneva, Ina; Zhelev, Petar; Cudlín, Pavel; Metslaid, Marek; Kankaanhuhta, Ville; Collet, Catherine; Annighöfer, Peter; Mathes, Thomas; Marianthi, Tsakaldimi; et al. (Forest Ecology and Management, 2023)
The relationship between the quality of forest seedlings and their outplanting survival and growth has long been recognized. Various attributes have been proposed to measure the quality of planted seedlings in forest regeneration projects, ranging from simple morphological traits to more complex physiological and performance attributes, or a combination thereof. However, the utility and meaning of seedling quality attributes can differ significantly among regions, nursery practices, site planting conditions, species and the establishment purpose. Here, forest scientists compiled information using a common agreed questionnaire to provide a review of current practices, experiences, legislation and standards for seedling quality across 23 European countries. Large differences exist in measuring seedling quality across countries. The control of the origin of seed and vegetative material (genetic component of plant quality), and control of pests and diseases are common practices in all countries. Morphological attributes are widely used and mandatory in most cases. However, physiological attributes are hardly used at the operative level and mainly concentrated to Fennoscandia. Quality control legislation and seedling quality standards are less strict in northern European countries where seedling production is high, and quality control relies more on the agreements between producers and local plant material users. In contrast, quality standards are stricter in Southern Europe, especially in the Mediterranean countries. The control of seedling quality based on plantation and reforestation success is uncommon and depends on the conditions of the planting site, the traditional practices and the financial support provided by each country. Overall, European countries do not apply the “target seedling concept” for seedling production except for seed origin. Seedling production in many countries is still driven by traditional “know-how” and much less by scientific knowledge progress, which is not adequately disseminated and ...